2016
DOI: 10.1108/mrr-06-2014-0145
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of perceived success in management consulting

Abstract: Purpose This paper aims to conceptualize perceived management consulting success, derive relevant success factors based on principal-agent theory and the resource-based view as well as investigate the particular factors’ influence. Management consulting has become important for improving the competitiveness of a variety of firms. Surprisingly, there is little empirical evidence clarifying what constitutes a successful management consulting project. Design/methodology/approach The authors conduct a survey to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 106 publications
0
11
0
1
Order By: Relevance
“…The study identifies six dimensions of engagement success: consultant's recommendation, client learning, and consultant performance. Bronnenmayer et al [46] find that from the consultants' viewpoint, the factors intensity of collaboration, common vision, consultant expertise, and top management support significantly influence perceived engagement success.…”
Section: Consulting Engagement Successmentioning
confidence: 99%
“…The study identifies six dimensions of engagement success: consultant's recommendation, client learning, and consultant performance. Bronnenmayer et al [46] find that from the consultants' viewpoint, the factors intensity of collaboration, common vision, consultant expertise, and top management support significantly influence perceived engagement success.…”
Section: Consulting Engagement Successmentioning
confidence: 99%
“…Tanulmányok vizsgálták a tanácsadói projektek sikerkritériumait (pl. : Appelbaum & Steed, 2005;Bronnenmayer, Wirtz & Göttel, 2016a, 2016b, az ügyfél-elégedettséget meghatározó főbb faktorokat (Roodhooft & Van den Abbeele, 2006) és tanácsadási szolgáltatásminőség dimenziókat (Ehrhardt & Nippa, 2005, Smith 2002, Wang, Shieh, & Hsiao, 2005, amely kutatások empirikus eredményekkel bővítették a vezetési tanácsadási szakirodalom ismeretanyagát.…”
Section: A Kritikai Perspektívaunclassified
“…It is without question that management consultancy is a business, and management consultants have to take a commercial approach to their work if they are to stay in business (Kipping and Clark 2012). Yet many writers have suggested that management consultants tend to be overfond of money (Bronnenmayer and Wirtz 2016). For example, they are often perceived to be working towards a follow-on contract with their clients as soon as they have been appointed, and as angling their advice so as to please those managers within their client organisations who can give them business (Bloch 1998;Sturdy et al 2009).…”
Section: Liberality: Never Giving Priority To Their Own Financial or mentioning
confidence: 99%